Efektivitas Larangan Merokok Terhadap Mahasiswa Fakultas Hukum UPN “Veteran” Jakarta Angkatan 2022 - Wulandari, Diah Ayu; Maniari, Elsa; Afifa, Erina Nur; Marito, Eugina Evita; Indiyarto, Fadhil Muhammad; Bakhtiar, Handar Subhandi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The Smoke-Free Zone is one of the efforts made by the government to protect the community, including passive smokers, from the dangers of exposure to cigarette smoke. Teaching and learning places (schools and universities) are one of the areas that are included in the category of Non-Smoking Areas (KTR), as well as the UPN